2018
DOI: 10.33549/physiolres.934004
|View full text |Cite
|
Sign up to set email alerts
|

Parabens and Their Relation to Obesity

Abstract: Parabens are a group of chemicals used as preservatives in the food, cosmetic and pharmaceutical industries. They are known to possess estrogenic effects, and therefore have been classified as endocrine disruptors. In addition to the classical endocrine organs, other tissues have endocrine activity, including adipose tissue. Several chemicals are known to cause obesogenic effects, and parabens are currently being studied in this context. The aim of this study was to investigate the possible connections of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…The direct and inverse associations between parabens and adiposity-related traits which we observed in this study did not reach significance. A recent study by Kolatorova et al showed higher concentrations of MeP and PrP in serum of obese compared to normal-weight individuals 65 , supporting the findings in a large Korean cohort 66 . Yet, a large cross-sectional study including 4,730 adults from NHANES found inverse associations between parabens and adiposity 36 .…”
Section: Discussionmentioning
confidence: 52%
“…The direct and inverse associations between parabens and adiposity-related traits which we observed in this study did not reach significance. A recent study by Kolatorova et al showed higher concentrations of MeP and PrP in serum of obese compared to normal-weight individuals 65 , supporting the findings in a large Korean cohort 66 . Yet, a large cross-sectional study including 4,730 adults from NHANES found inverse associations between parabens and adiposity 36 .…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies examining prenatal paraben exposure have reported inconsistent associations with fetal growth, with varying estimated directions and magnitude of effect (24)(25)(26)(64)(65)(66). More broadly, however, parabens are suspected to have effects on body composition and altered weight (67)(68)(69)(70)(71). For example, a study in the National Health and Nutrition Examination Survey (NHANES) reported that higher urinary parabens were associated with lower BMI in both children and adults (69).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining prenatal paraben exposure have reported inconsistent associations with fetal growth, with varying estimated directions and magnitude of effect (19)(20)(21)(54)(55)(56). More broadly, however, parabens are suspected to have effects on body composition and altered weight (57)(58)(59)(60)(61). For example, a study in the National Health and Nutrition Examination Survey (NHANES) reported that higher urinary parabens were associated with lower BMI in both children and adults (59).…”
Section: Discussionmentioning
confidence: 99%